1997
DOI: 10.2337/diab.46.11.1743
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsense Mutation in the Inward Rectifier Potassium Channel Gene, Kir6.2, Is Associated With Familial Hyperinsulinism

Abstract: ATP-sensitive potassium (K[ATP]) channels are an essential component of glucose-dependent insulin secretion in pancreatic islet beta-cells. These channels comprise the sulfonylurea receptor (SUR1) and Kir6.2, a member of the inward rectifier K+ channel family. Mutations in the SUR1 subunit are associated with familial hyperinsulinism (HI) (MIM:256450), an inherited disorder characterized by hyperinsulinism in the neonate. Since the Kir6.2 gene maps to human chromosome 11p15.1 (1,2), which also encompasses a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(72 citation statements)
references
References 20 publications
0
72
0
Order By: Relevance
“…The most commonly deleted region of chromosome 11 contained the SUR1 [25]and KIR6.2 [26]genes that code for two subunits of the potassium-ATP channel and are involved in familial recessive PHHI [3, 4, 5, 6, 7]. To understand whether the LOH may also unmask a recessive phenotype responsible for hypersecretion of insulin, we looked for deleterious mutations in the SUR1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly deleted region of chromosome 11 contained the SUR1 [25]and KIR6.2 [26]genes that code for two subunits of the potassium-ATP channel and are involved in familial recessive PHHI [3, 4, 5, 6, 7]. To understand whether the LOH may also unmask a recessive phenotype responsible for hypersecretion of insulin, we looked for deleterious mutations in the SUR1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of patients with diazoxide and/or somatostatin analogues is not always effective, necessitating an intervention such as pancreatectomy [2]. Rare familial forms may be caused by recessive or dominant defects in four different genes: (1) the sulphonylurea receptor gene (SUR1) [3, 4, 5]; (2) the inward rectifying potassium channel subunit gene (KIR6.2) [6, 7]; (3) the glutamate dehydrogenase gene (GLUD-1) [8], and (4) the glucokinase gene (GK) [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In the search for possible involvement of K ATP channel mutations in pathology, a rare genetic disease called persistent hypoglycemic hyperinsulinemia of infancy was shown to be due to a mutation of the SUR1 gene which leads to permanent closure of the channel [27, 28] and a resultant non-regulatable and exaggerated insulin secretion. In one case, a Kir 6.2 mutation appears to be associated with a familial hyperinsulinism [29]. In the multigenic NIDDM disorder, it was observed that certain mutations of SUR1 occur slightly more frequently in NIDDM patients than in control subjects [30] leading, in some patients, to a decreased sensitivity to sulfonylureas [31].…”
Section: Possible Role(s) Of -Endosulfine In Pathologymentioning
confidence: 99%
“…More recently, however, physiological and morphological studies have made it clear that PHHI is a hyperfunctional disorder of the beta cells associated with heterogeneous pathologic changes [3,14,26]. Recently, molecular studies have revealed that PHHI results from at least three basic genetic defects: first, loss-of-function mutations on chromosome locus 11p15.1 affecting the genes of the two subunits SUR1 and KIR6.2 [11,24,34], which form the ATP-dependent potassium channel that is an integral part of the stimulus-secretion coupling apparatus of insulin release; second, gain-of function mutations of genes for enzymes (glucokinase, glutamate dehydrogenase) that regulate the rate of insulin secretion; and third, a two-hit loss-of-heterozygosity (LOH) mechanism in a group of beta cells [9,10], with a specific loss of maternal alleles of the imprinted chromosome region 11p15.1 unmasking a paternally inherited recessive SUR1 or KIR6.2 mutation (for further review cf. [23]).…”
Section: Introductionmentioning
confidence: 99%